Metabolic impact of a soccer match on female players - Gravina, L.; Ruiz, F.; Lekue, J. A.; Irazusta, J.; Gil, S. M. (Journal of Sports Sciences, 2011)
The aim of this study was to examine the metabolic effect of a female soccer match in elite and sub-elite teams. Blood samples were taken (24 h before, immediately after and 18 h after official soccer matches) to determine haematological, electrolytic and hormonal variables, as well as the levels of cell damage and oxidative stress in 14 elite and 14 sub-elite players. Our results show increases in white blood cell count (P < 0.001) and the percentage of neutrophils (P < 0.001), and decreases in the percentage of lymphocytes (P < 0.05), eosinophils (P < 0.001), monocytes (P < 0.001) and basophils (P < 0.05) immediately post-match. Increases were also found in lactate dehydrogenase activity (P < 0.001), uric acid (P < 0.001), albumin (P < 0.001), total antioxidant status (P < 0.001) and free testosterone levels (P < 0.01). Creatine kinase activity significantly increased 18 h post-match (P < 0.01) and the concentrations of several ions, glucose and proteins were found to be altered immediately post-match. Overall, our results show that playing a soccer match exerts specific metabolic effects on female players, resulting in muscle damage, oxidative stress and biochemical and hormonal variations. On the basis of some interesting correlations, we also suggest that exercise-induced cell breakdown may enhance antioxidant capacity of the soccer players.